Preliminary evaluation of CMAQ modelled wet deposition of sulphur and nitrogen over Bulgaria. (11th April 2019) - Georgieva, Emilia; Hristova, Elena; Syrakov, Dimiter; Prodanova, Maria; Batchvarova, Ekaterina
Wet depositions of sulphur and nitrogen over Bulgaria have been simulated by the WRF-CMAQ system for the period from March to June 2016. Precipitation amounts have been overestimated - the average NMB is 44% for the country and 70% for Sofia. Precipitation chemistry data from Sofia have been used for the estimation of observed sulphur and nitrogen depositions - 602 mg m −2, and 528 mg m −2, respectively. Modelled wet depositions show overestimation, more significant for sulphur deposition (NMB 87%). Precipitation adjustment has been applied as post-processing to model wet depositions. The correction led to decrease in NMB for S wet deposition (9%), while N- monthly depositions were in general underestimated. Possible effects of long-range transport for Sofia have been discussed for two selected periods of a few days.